Classification of the metallo β-lactamase subtype produced by the carbapenem-resistant Pseudomonas aeruginosa isolates in Japan. Issue 2 (February 2022) - Nakayama, Ryo; Inoue-Tsuda, Megumi; Matsui, Hidehito; Ito, Tamaki; Hanaki, Hideaki
Abstract: Introduction: Multidrug resistant microorganisms are a serious threat to human health. Under the circumstances, a front line of antimicrobials in clinical setting may be carbapenem β-lactams (CRBP). However, emergence of CRBP resistant (CRBP-r) Gram-negative bacteria are the most alarming. CRBP-r is mainly caused to the production of β-lactamase, down and up expression of the diffusion channel and the efflux pump genes, respectively. Among them, production of metallo-β-lactamase (MBL) is a major cause of high-level of CRBP-r. Method: We analyzed the MBL subtypes by PCR and DNA sequencing in CRBP-r Psudomonas aeruginosa in the collection of the joint program by the Japanese Association for Infectious Diseases, Japan Society for Clinical Microbiology and Japanese Society of Chemotherapy (2006–2015 in Japan). Results: Among 275 strains out of a total 1716 isolates, 23 (8.3%) were MBL-positive exhibiting resistant to meropenem (MEPM), imipenem, ceftazidime, cefepime, ciprofloxacin and levofloxacin without exception and the MIC of MEPM appeared over 128 μg/mL. Their MBL subtype analysis revealed that 16, 2, and 2 isolates were IMP-1, IMP-7 and VIM-2 positive, respectively, and one isolate each expressed either IMP-10, IMP-34 or IMP-41. Conclusions: This study revealed that all the MBL-positive CRBP-r isolates were highly resistant to carbapenems dominating IMP-1 production.